Dividends and economic policy uncertainty: International evidence - Attig, Najah; El Ghoul, Sadok; Guedhami, Omrane; Zheng, Xiaolan (Journal of Corporate Finance, 2021)
We provide the first international evidence on the impact of economic policy uncertainty (EPU) on dividend policy. Using data from 19 countries, we find that a high level of EPU is positively associated with dividend payout. This evidence is robust to using alternative dividend payout measures, to controlling for other sources of uncertainty, and to addressing endogeneity. We further find that the effect of EPU on dividend policy is moderated by firms' free cash flows and governance quality, and by the quality of country-level indicators of shareholder protection, disclosure, enforcement, and creditor protection. Collectively, our novel evidence suggests that dividends help mitigate agency problems during high-EPU periods.